E-wallets as a Payment Instrument for Digital Nomads - Majewska, Julia (E-portfele jako instrument płatności cyfrowych nomadów, 2025)
Aim: The aim of the paper was to examine the determinants affecting the number of e-wallets (Stored Value Digital Wallets) owned by digital nomads, highlighting the features of digital wallets that differentiate them from other available money storage options. Methodology: The research methods applied were literature analysis, in-depth interviews, and the Pearson correlation coefficient. Results: When conducting the Pearson correlation analysis, it should be emphasised that the strongest correlation with the number of e-wallets owned was related to the number of countries visited by digital nomads in a year and the number of employers/clients. After analysing the in-depth interviews, the main determinant for having e-wallets was their usefulness, popularity, and ease of use. Implications and recommendations: The conducted research may constitute the basis for further research on the use of new technologies by digital nomads. Originality/value: The paper describes the identified research gap related to the use and perception of e-wallets by digital nomads.
Ekonomia XXI Wieku = Economics of the 21st Century, 2025, Nr 28, s. 1-8
Keywords: digital nomads; e-wallet; online payments; cyfrowi nomadzi; e-portfele; płatności online